(untitled) (Al-Aasar, 2025)
The issue of gender transition has emerged in recent decades not only as a product of scientific and medical advancements but also as a central point of legal, social, and religious debates. International human rights bodies and activists increasingly recognize gender identity as a fundamental human right, emphasizing the individual’s autonomy to choose and express their identity. The Universal Declaration of Human Rights (1948), the International Covenant on Civil and Political Rights (ICCPR 1966), and the International Covenant on Economic, Social and Cultural Rights (ICESCR 1966) do not explicitly mention “transgender” individuals. However, through the principle of non-discrimination, modern interpretations have brought the transgender community within the scope of legal protections. The Yogyakarta Principles (2006) further provided specific guidelines on sexual orientation and gender identity, which have significantly influenced legislative frameworks across various states. In Western contexts such as Europe and the United States, courts and parliaments have expanded rights for transgender persons, while in South Asia, countries like India and Pakistan have introduced legal reforms aimed at protecting this community and ensuring equality. In contrast, Islamic law does not perceive gender identity solely as a social or psychological matter but rather as a divinely ordained and juridical issue. The Qur’an identifies humanity in the binary categories of “male” (dhakar) and “female” (untha), and classical jurists elaborated rulings regarding khuntha (intersex individuals) centuries ago. Contemporary Islamic legal institutions, such as the International Islamic Fiqh Academy (Jeddah), have clarified that medical intervention is permissible when a person is biologically intersex and the ambiguity can be resolved. However, elective or voluntary gender reassignment undertaken by individuals without biological necessity is deemed impermissible in Shariah. This highlights a crucial distinction: while Islamic law differentiates between congenital ambiguity and elective transformation, international law tends to prioritize self-identification as the decisive factor. This comparative study illustrates that international legal systems place absolute emphasis on personal autonomy and self-expression, whereas Islamic law situates freedom within the boundaries of Shariah and the higher objectives of Islamic jurisprudence (Maqasid al-Shariah). Nevertheless, both systems share certain common ground, particularly in recognizing the inherent dignity of human beings, the pursuit of justice, and the elimination of discrimination. Yet, the application of these principles diverges sharply: Western legal systems increasingly guarantee full legal equality for transgender individuals, while Muslim societies, shaped by deep-rooted religious and cultural sensitivities, often display resistance. The resulting tension reflects a broader civilizational and intellectual contest between universalist human rights frameworks and religious legal traditions. The findings of this research suggest that no unilateral resolution can adequately address the complexities of this issue. Global human rights discourses must account for local religious and cultural contexts to remain relevant and effective. Simultaneously, Islamic law possesses foundational principles rooted in human dignity, balance, and justice, which can be interpreted in ways that engage contemporary challenges without abandoning core doctrinal commitments. A reconciliatory framework is therefore both possible and necessary: one that safeguards the rights and welfare of transgender individuals while respecting the normative boundaries of Shariah. Such an approach would not only mitigate conflict between international and Islamic legal orders but also contribute to a more nuanced and pluralistic understanding of human rights in the modern era.